Glucagon‐like peptide‐1 receptor agonists and microvascular outcomes in type 2 diabetes: A systematic review and meta‐analysis. Issue 1 (3rd September 2018) - Avgerinos, Ioannis; Karagiannis, Thomas; Malandris, Konstantinos; Liakos, Aris; Mainou, Maria; Bekiari, Eleni; Matthews, David R.; Tsapas, Apostolos
Abstract : We conducted a systematic review and meta‐analysis of randomized controlled trials to assess the effect of glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) on microvascular endpoints in adult patients with type 2 diabetes. We included 60 studies with 60 077 patients. GLP‐1 RAs marginally reduced urinary albumin‐to‐creatinine ratio compared with placebo or other antidiabetic agents (weighted mean difference − 2.55 mg/g; 95% confidence interval [CI] −4.37 to −0.73 and −5.52; −10.89 to −0.16, respectively) and had no clinically relevant effect on change in estimated glomerular filtration rate. Treatment with GLP‐1 RAs did not increase incidence of diabetic retinopathy, macular oedema, retinal detachment and retinal haemorrhage, irrespective of comparator. Nevertheless, incidence of vitreous haemorrhage was higher in subjects treated with GLP‐1 RAs compared with placebo (odds ratios 1.93; 95% CI 1.09 to 3.42). In conclusion, GLP‐1 RAs are safe regarding nephropathy‐ and retinopathy‐related outcomes. Caution may be warranted for incidence of vitreous haemorrhage. The low overall quality of evidence highlights the need for consistent assessment and reporting of microvascular endpoints in future trials.